A Study of the prevalence of human intestinal parasites in some primary school children in Houn city, Libya - Zaed , Hana Abd Alslam (مجلة البحوث الأكاديمية, 2018)
Background: Intestinal parasites cause significant morbidity and mortality throughout the world. The prevalence of intestinal parasites is not recorded in the population of primary school children in Houn city, Libya.Objectives:An epidemiological survey was carried out in Houn city to collect baseline data on the prevalence of intestinal parasitic infections among some primary school children in Houn city, Libya. Materials and Methods: a total of 600 stool samples (during January, February and March 2016) were collected from randomized population of some primary school children in Houn city. All stool specimens were examined by direct-smear microscopy, and formalin-ether sedimentationmethod for the detection of intestinal parasites in normal saline and Lugol's iodine preparations.